2022
DOI: 10.1186/s12917-022-03356-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Mycobacterium tuberculosis complex in elephants through a One Health approach: a systematic review

Abstract: Background Mycobacterium tuberculosis complex (MTC) that causes the chronic infectious disease- tuberculosis (TB), often presents with a complicated epidemiological pattern where the transmission chain may include humans, domestic animals and wildlife, including elephants. TB has been reported globally in both captive and wild elephants. The One Health approach might be the most effective way of understanding the shared MTC infection dynamics in captive and wild animals like Asian elephants. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Case E1’s history of living within a city household, along with disease onset so soon after arrival, suggests this bear was the index case in the Lineage 1 outbreak, and highlights the risk to bear sanctuaries receiving bears with a history of co-habiting with humans. Given the anthropozoonotic spread of TB in other species with human contact 17 , 20 , 42 , along with the high numbers of sun bears and Asiatic black bears held in captivity (legally and illegally) in high TB burden regions 56 – 60 , it is surprising this is the first report of incidental spill-over from humans to these species. Regardless, our findings confirm that both bear species are susceptible to human lineages of M. tuberculosis and should inform sanctuary disease screening strategies.…”
Section: Discussionmentioning
confidence: 98%
“…Case E1’s history of living within a city household, along with disease onset so soon after arrival, suggests this bear was the index case in the Lineage 1 outbreak, and highlights the risk to bear sanctuaries receiving bears with a history of co-habiting with humans. Given the anthropozoonotic spread of TB in other species with human contact 17 , 20 , 42 , along with the high numbers of sun bears and Asiatic black bears held in captivity (legally and illegally) in high TB burden regions 56 – 60 , it is surprising this is the first report of incidental spill-over from humans to these species. Regardless, our findings confirm that both bear species are susceptible to human lineages of M. tuberculosis and should inform sanctuary disease screening strategies.…”
Section: Discussionmentioning
confidence: 98%
“…TB among captive elephant populations is investigated using several methodologies, for example, blood serum sampling and lateral flow serological testing [112] and/or collection of material through trunk washing, culture, and PCR testing [113]. However, current methodologies are limited, and infection rates in populations are difficult to quantify conclusively [114,115]. One study, using blood serum sampling of approximately 600 captive Asian elephants found a positive TB prevalence rate of 16% [112], and another study, also using serology, found 23% in a captive population [22].…”
Section: Tuberculosis and Elephantsmentioning
confidence: 99%
“…In addition, there are approximately 126 captive or managed African elephants reported in South Africa 4 . These elephant populations face further threats from infectious pathogens, such as elephant endotheliotropic herpesvirus (EEHV) 5 and tuberculosis (TB) 6 8 . The presence of disease in these populations can lead to detrimental consequences for the maintenance of a stable ecological niche 9 .…”
Section: Introductionmentioning
confidence: 99%